Defining the production scale of an underground mine. - Ding, B. (The International Journal of Mineral Resources Engineering)
In the mining industry, the production scale of a mine operation has been defined as the eproduction rate, or the mine capacity. The production level, another important criterion of the production scale, has been neglected. Such a misconception of the production scale may cause improper definition of the capacity, and therefore cause serious problems of the future mine operations. In fact both the production rate and level affect the mining economy in different ways and one affects the determination of the other. This paper demonstrates how the production rate and level influences the mining operation economically, examines the interrelationships between these two parameters, and illustrates how to determine the mine production scale by looking at both the production rate and production level definition.This paper is based on the researches on hardrock mining cases, but the application of the principles delivered may be extended to the other types of mines, provided that their special characteristics are considered.